In vitro and in vivo assessment of antiproliferative, apoptotic and antitumorigenic effects of cardamonin against hepg2 hepatocellular carcinoma cells / Nassrin Abdulgalel Badroon - Nassrin Abdulgalel , Badroon (2022)
Cardamonin (2′, 4′-dihydroxy-6′-methoxychalcone) is a natural bioactive chalcone that has been explored with keen interest by investigators because of its broad-spectrum biological activities. Previous studies revealed that Cardamonin (CADMN) has antiproliferative activities against several types of cancer cells, including lung, prostate, breast, nasopharynx, multiple myeloma, ovarian and colorectal. The present study investigated the antiproliferative, apoptotic and antitumorigenic effects of CADMN against HepG2 hepatocellular carcinoma cells in vitro and in vivo in HepG2 cells xenografts in nude mice. Results of the in vitro study showed that CADMN inhibited the growth of HepG2 cells with an IC50 4.6 ± 0.16 μg/ml after 72 h of treatment. Cell cycle analysis showed that CADMN arrests HepG2 cells at the G1 phase. Moreover, AO/PI double staining assay indicates gradual cell death via apoptosis as evidenced by the morphological changes sequential from 24 h to 72 h in CADMN-treated HepG2 cells. Then, the CADMN-treated and vehicle-treated (control) HepG2 cells were stained with Annexin V-FITC and PI and analysed by flow cytometry. The CADMN-treated cells showed an increment of early and late apoptosis in a time-dependent manner, which peaked at 31.9% and 35.6%, respectively, after 72 h treatment. Findings also showed that apoptosis induction occurred via extrinsic and intrinsic pathways as demonstrated by a significant increase in caspases-3/7, -8, and -9 activities and overexpression of apoptotic proteins using proteome profiler array. The results of the confocal microscope revealed that CADMN induces alterations in cell membrane permeability and mitochondrial outer membrane permeabilization (MOMP) and significantly increases cytochrome C release into the cytosol. In addition, CADMN generated significantly reactive oxygen species (ROS) production in HepG2 cells after 2 h of treatment compared to control. Furthermore, CADMN inhibited NF-κβ translocation in HepG2 cells, which suggests the contribution of NF-κβ inhibitory mechanism in apoptosis through the ROS accumulation. Oral acute toxicity study in mice showed that CADMN is safe up to 2000 mg /kg. As compared to the untreated control group, the oral administration of 25 and 50 mg/kg/day of CADMN in xenograft nude mice showed significant suppression of tumour growth by 45.4% and 65.2%, respectively. Immunohistochemistry findings showed that Ki-67 and PCNA proliferating proteins were strongly overexpressed in the untreated control group. In contrast, these proteins were downregulated in mice treated with 25 and 50 mg/kg of mg/kg/day of CADMN. Immunofluorescence results of tumour tissues showed high expression levels of Bcl-2, p-NF-κβ, and Ikkβ, while 50 mg/kg/day of CADMN treatment significantly downregulated these proteins. In conclusion, these results suggest that CADMN has an anti-proliferative effect, apoptotic action and anti-tumorigenic activity on hepatocellular carcinoma HepG2 cells and can be considered as a potential alternative anticancer agent against hepatocellular carcinoma. However, further investigations should be conducted in different primary liver cancer cells to represent the heterogeneity of hepatocellular carcinoma.